Autoimmune Hemolytic Anemia Associated with Mature Ovarian Cystic Teratoma Containing Monoclonal Immunoglobulin G: A Case Report and Review of Literature - Yuma Nato; Keiki Nagaharu; Keika Itoh; Naoki Shinke; Keiko Maeyama; Akihiko Sawaki; Hiroyuki Miyashita (Case Reports in Obstetrics and Gynecology)
Background. Autoimmune hemolytic anemia (AIHA) associated with solid tumors such as mature cystic teratomas is rare and poorly understood. Here, we report a successfully treated case of secondary AIHA in a mature cystic teratoma containing antibodies against red blood cells. Case description. A 22-year-old woman was referred to our hospital with progressive anemia. Laboratory findings revealed hemolysis with a positive direct and indirect antiglobulin test. Imaging studies identified a left ovarian mass, suspected to be a mature cystic teratoma, which was later confirmed by histopathology after laparoscopic oophorocystectomy. The patient was treated with prednisolone, resulting in improved anemia. To examine the relationship between the tumor and AIHA, an indirect antiglobulin test was performed on the tumor contents. Stronger aggregations were observed at any concentration diluted by 10 times from 10 to 10,000 times of the tumor contents compared to the patient’s serum. Additionally, immunofixation electrophoresis of the tumor contents revealed the presence of monoclonal immunoglobulin G-κ. Conclusion. The presence of monoclonal IgG-κ in the tumor suggests intratumoral antibody production as a possible mechanism. Further research is necessary to elucidate the pathogenic relationship between such tumors and AIHA. The report also highlights the importance of considering secondary AIHA in patients with unexplained anemia and solid tumors.